The wearable cardioverter-defibrillator: experience in 153 patients and a long-term follow-up - Rosenkaimer, Stephanie L.; El-Battrawy, Ibrahim; Dreher, Tobias C.; Gerhards, Stefan; Röger, Susanne; Kuschyk, Jürgen; Borggrefe, Martin; Akın, Ibrahim (Journal of Clinical Medicine, 2020)
Background: The wearable cardioverter-defibrillator (WCD) is available for patients at high risk for sudden cardiac death (SCD) when immediate implantable cardioverter-defibrillator (ICD) implantation is not possible or indicated. Patient selection remains challenging especially in primary prevention. Long-term data on these patients is still lacking. Methods: 153 patients were included in this study. They were prescribed the WCD between April 2012 and March 2019 at the University Medical Center, Mannheim, Germany. The mean follow-up period was 36.2 ± 15.6 months. Outcome data, including all-cause mortality, were analyzed by disease etiology and ICD implantation following WCD use. Results: We analyzed 56 patients with ischemic cardiomyopathy, 70 patients with non-ischemic cardiomyopathy, 16 patients with prior need for ICD/CRT-D (device for cardiac resynchronization therapy with defibrillator) explanation, 8 patients with acute myocarditis and 3 patients with congenital diseases. 58% of the patients did not need ICD/CRT-D implantation after WCD use. 4% of all patients suffered from appropriate WCD shocks. 2 of these patients (33%) experienced appropriate ICD shocks after implantation due to ventricular tachyarrhythmias. Long-term follow-up shows a good overall survival. All-cause mortality was 10%. There was no significant difference between patients with or without subsequent ICD implantation (p = 0.48). Patients with ischemic cardiomyopathy numerically showed a higher long-term mortality than patients with non-ischemic cardiomyopathy (14% vs. 6%, p = 0.13) and received significantly more ICD shocks after implantation (10% of ischemic cardiomyopathy (ICM) patients versus 3% of non-ischemic cardiomyopathy (NICM) patients, p = 0.04). All patients with ventricular tachyarrhythmias during WCD use or after ICD implantation survived the follow-up period. Conclusion: Following WCD use, ICD implantation could be avoided in 58% of patients. Long-term follow-up shows good overall survival. The majority of all patients did not suffer from WCD shocks nor did receive ICD shocks after subsequent implantation. Patient selection regarding predictive conditions on long-term risk of ventricular tachyarrhythmias needs further risk stratification.
Gesehen am 10.12.2020